Long-term safety, efficacy, and patient acceptability of teriparatide in the management of glucocorticoid-induced osteoporosis - Dore, Robin K (Dove Medical Press, 2013)
Glucocorticoids are commonly prescribed medications to treat multiple diseases across many medical specialties. One of the most common yet largely unappreciated side effect of glucocorticoid use is increased risk of fracture. Many different therapies are indicated to prevent and treat this condition; many guidelines exist that suggest appropriate use of both glucocorticoids and the medications approved to prevent this common side effect of glucocorticoid therapy. Nevertheless, 30%–50% of patients on long-term glucocorticoid therapy sustain a fracture. Teriparatide, recombinant human parathyroid hormone (1–34), is a daily self-injectable therapy for 24 months approved for use in patients taking long-term glucocorticoids. Teriparatide has been shown to increase bone mineral density and reduce vertebral fracture risk in glucocorticoid-treated patients. Glucocorticoids have many adverse effects on bone that teriparatide has been shown to prevent or negate. Given the fact that preventive therapy for glucocorticoid-induced osteoporosis is often not prescribed, one wonders whether a daily self-injectable therapy for this condition would be prescribed by physicians and accepted by patients. This article reviews the epidemiology, pathophysiology, treatment, guidelines, and persistence data (when available) for patients with glucocorticoid-induced osteoporosis treated with teriparatide.